Advancement of STEM-Based Digital Module to Enhance HOTS of Prospective Elementary School Teachers - Ramadhani, Dini; Kenedi, Ary Kiswanto; Rafli, Muhammad Febri; Handrianto, Ciptro (FKIP Universitas Lampung, 2022)
Advancement of STEM-Based Digital Module to Enhance HOTS of Prospective Elementary School Teachers. Objectives: The goal of this research was to develop a valid, practical, and effective STEM-based digital module to help prospective elementary school teachers enhance their HOTS. Methods: This was a development study employing a four-dimensional model. This study enlisted the help of five lecturers and 100 prospective elementary school teachers. Findings: The developed STEM-based digital module is declared to be highly valid to use with score obtained is 3.38 and also said to be highly practical to utilize, with a lecturer aspect score of 95.67 and a student aspect score of 91.37. The STEM-based digital module also is declared effective in strengthening the HOTS of prospective elementary school teacher students which received an N-Gain score of 0.69 in the medium category. Conclusion: The study's findings revealed that a valid, practical, and effective STEM-based digital module has been established to enhance the HOTS of prospective elementary school teachers.Keywords: prospective teacher, digital module, STEM, HOTS.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202245